Integration of Nutritional Inputs for Improving Rice Productivity in Laterite Soils - Jinappa Halingali (Department of Agronomy, College of Horticulture, 2003)
A study on "Integration of nutritional inputs for improving nee productivity in laterite soils" was taken up during 2001-2003 at the College of Horticulture, Vellanikkara The experiment consisted of 17 treatments including two sources of organic manure and two levels of nutrition with combinations of lime and silica to develop a cost effective, high yield and sustainable production technology for rice by identifying the components of good management. The treatment .receiving poultry manure with 90 kg ha" of fertilizer N and 500 kg ha" of silica recorded the maximum height productive tillers, •number of spikelets per panicle and thousand grain weight which . contributed to the maximum grain yield 0[7004 kg ha". An increase in 1680 kg grain yield and 1087 kg straw yield than the package of practices recommendation of Kerala Agricultural University appear to be due to the application of Silica, substitution of cow dung by the poultry manure and increased dose of N with an organic: inorganic ratio of 1 :2.25, increased dose ofK and reduced dose ofP. Cow dung contains Fe, Zn and Cu in toxic levels to rice. Poultry manure has the content of these elements in far less quantities but has higher Ca content . which helps in reducing the uptake of unfavourable elements by the rice plants. Increase in'the level of K application @120 kg ha' has recorded 1387 kg ha" more grain than the present recommendation of 35 kg ha" and the uptake of K by the plants are far above the applied levels. This suggests that the present recommendation of35 kg ha' ofK has to be enhanced up to 120 kg ha" to prevent the soil degradation. It is also seen that the rice plants absorb only around 20 kg P and hence the P recommendation can be reduced from 35 kg to 20 kg ha".